Efektifitas Teknik Relaksasi Genggam Jari Dan Nafas Dalam Terhadap Penurunan Dismenore - Sri - Ramadina; Sri - -; Jumaini - - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of this research was to determine effectiveness of relaxation techniques of handheld finger and deep breathing to decrease dysmenorrhea. The method of this research was quasi - experimental and used non - equivalent control group as the research design. This research was conducted at SMP 3 Pekanbaru that consist of 30 people, 15 people were experimental group and 15 people were control group. The sampling method was purposive sampling. Measuring instruments was the observation sheet. The analysis that was used in this research were univariate and bivariate analysis with used t - dependent and t-independent test. The results showed significant differences in the changes of dysmenorrhea intensity in the experimental group after being given a handheld finger relaxation techniques and deep breathing and the control group were not given a handheld finger relaxation techniques and deep breathing with a p-value (0,000) < α (0,05). The results of this research recommends the provision of finger relaxation techniques and deep breathing in young women who got dysmenorrhea as a alternative therapy that was effective in reducing dysmenorrhea. Keywords : Deep breathing,dysmenorrhea, handheld fingers